PENGARUH STRUKTUR AKTIVA DAN PERTUMBUHAN PENJUALAN TERHADAP NILAI PERUSAHAAN DENGAN STRUKTUR MODAL SEBAGAI VARIABEL INTERVENING (Studi Empiris Pada Perusahaan Sub Sektor Makanan Dan Minuman Yang Terdaftar Di BEI Tahun 2017-2019) - Akmaris, Corintania Byand; Wahyuni, Ika; Pramitasari, Triska Dewi (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
The influence of asset structure and sales growth on firm value through capital structure in food and beverage sub-sector companies listed on the Indonesia Stock Exchange in 2017-2019. Each company has a goal to earn profits or profits that are able to maintain the viability of the company. To achieve this goal, it is necessary to have good financial management so that company finances can be managed effectively and efficiently. The purpose of this study was to analyze and examine the effect of asset structure and sales growth on firm value through capital structure. The population in this study were 26 food and beverage companies listed on the IDX. The sampling technique was determined by purposive sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that asset structure has no significant effect on capital structure, sales growth has a significant effect on capital structure, asset structure has no significant effect on firm value, sales growth has no significant effect on firm value, capital structure significant effect on firm value. The results of the indirect effect hypothesis test show that both asset structure and sales growth have no significant effect on firm value through capital structure.